Basic Directions Of Ecological Tourism Functioning In Russia At The Present Time - Moishevich Eidelman, Boris (2019)
The paper considers the current development of ecological tourism in the Russian Federation. The causes of backwardness of Russia from the leading countries in the development of ecological tourism are presented. This work reveals the enormous potential that the Russian Federation possesses in terms of the ecological tourism development and describes many specially protected natural areas that can contribute to its brisk growth.The authors identified the main barriers to the development of ecological tourism in Russia. The role and importance of city parks in the development of eco-tourism are illustrated by the example of creating a park for recreation and reading named after G. Tukay in the city of Nizhnekamsk, Republic of Tatarstan.The main functions performed by modern city parks to familiarize the population with nature, the desire to preserve nature objects and increase interest in ecological tourism are described.